The Antioxidant Effects of Calligonum Extract on Oxidative Stress in Spermatogonial Stem Cells Culture - Shirin Barati; Mansoureh Movahedin (Tabriz University of Medical Sciences, 2021)
Background: Spermatogenesis is a programmed route for germ cell proliferation and differentiation that can produce abundant numbers of spermatozoa. The antioxidants play a vital role in decreasing oxidative stress production in cells; therefore, the extraction of plants with antioxidant property can prevent cell damage. In the present study, antioxidant effects of Calligonum extract on proliferation and colonization rate of spermatogonial cells were assessed. Methods: After isolation and culturing of spermatogonial stem cells (SSCs) on neonatal mice (4-5 days old) and identification by PLZF and Oct4 markers, the therapeutic effect of Calligonum comosum extract on cells treated with H2O2 was measured. The cultured cells were divided into four groups: Control, Calligonum, H2O2 and Calligonum + H2O2 groups. Induced oxidative stress cells were treated with 10 μg/ml extract for 3 weeks. Reactive oxygen species (ROS) levels were assessed by the flow cytometry, and proliferation and total antioxidant capacity (TAC) were evaluated by cell count and ferric reducing ability of plasma (FRAP) assay, respectively. Also, the apoptosis rate was measured with P53 and Bax genes by the real- time PCR method. Results: After three-week treatment, ROS level was significantly lower in the Calligonum group than in the H2O2 group. Antioxidants levels were significantly higher in Calligonum group than in the H2O2 group (P≤0.05). There was also a strong inverse relationship between the two groups. Proliferation and colonization rate were significantly higher in Calligonum + H2O2 group than in H2O2 group (P≤0.05). Finally, the results suggested that P53 and Bax expression decreased in Calligonum + H2O2 group compared to H2O2 group. Conclusion: The results of present study revealed that 30 μM doses of H2O2 increased oxidative stress and apoptosis on the one hand and decreased proliferation of SSCs on the other hand. Asa plant with antioxidant effect, Calligonum could reduce the level of ROS and apoptosis, and increase proliferation, colonization rate and TAC.